ACCURACY OF CONE BEAM COMPUTED TOMOGRAPHY (CBCT) IN ENDODONTICS: A STUDY OF COMPARISON OF CBCT VS. DIGITAL INTRA-ORAL PERI-APICAL RADIOGRAPHS IN THE EVALUATION OF PERIAPICAL RADIOLUCENCY IN ENDODONTICS - Pervez, Jazib; Adil, Hafiz Muhammad; Zafar, Ifrah; Rana, Mehmood Ahmed; saeed, Aalia; Akram, Anam (Pakistan Oral & Dental Journal, 2023)
CBCT is a newer technology, that utilizes a cone-shaped beam of ionizing radiation and advanced reconstruction algorithms to generate a 3-D reconstruction of the maxillofacial region, has superior imaging capabilities over traditional 2-D Digital Intra-oral Peri-Apical Radiographs (IOPAR). CBCT represents an accurate evaluation of root canal morphology, peri-apical pathology, and dental anomalies. However, CBCT carries the drawback of increased radiation exposure and high cost. Our study compares the diagnostic accuracy of Cone Beam Computed Tomography (CBCT) vs. Digital Intra-oral Peri-Apical Radiographs (IOPAR) in the assessment of periapical radiolucency in post endodontic cases, while contributing to the existing literature on CBCT’s role in endodontics.A sample of 105 teeth from 60 patients were included in the study, with endodontic treatment within the past six months. The detection of periapical radiolucency was evaluated, using CBCT as the gold standard. Statistical analysis, including the Chi-Square test and odds ratio analysis, were conducted to compare the diagnostic performance of CBCT and IOPAR.CBCT exhibited a higher sensitivity (100%) and specificity (57.14%) compared to IOPAR in detecting periapical radiolucency. However, the observed difference between the two imaging modalities was not statistically significant (p > 0.05). The odds ratio analysis indicated a 1.7 times greater chances of detecting periapical lesions when employing CBCT as the diagnostic modality.CBCT has better accuracy than IOPAR in detecting periapical radiolucency in post-endodontic cases. However, further research is required for evidence-based recommendations for routine use of CBCT in endodontics.
Keywords: Cone beam computed tomography; Endodontics; Intraoral periapical radiograph; Periapical lesion